Propolis: lymphocyte proliferation and IFN-gamma production - Sa-Nunes, A.; Faccioli, L. H.; Sforcin, J. M. (Elsevier B.V., 2003)
We evaluated propolis influence on polyclonal activation of lymphocytes by concanavalin A (Con A). The in vitro experiments showed that propolis decreases splenocyte proliferation both in the absence or presence of Con A. The supression in mitogen-induced splenocyte proliferation also occurred when mice were treated intraperitoneally with propolis for 3 days. An increased of IFN-gamma production in the culture supernatants of the same cells was, observed. A dual action of propolis on lymphocyte activation was proposed: it decreases splenocyte proliferation in the presence or absence of Con A and stimulates IFN-gamma production by spleen cells. These results are important to understand the immunomodulatory action of propolis on the host's specific and non-specific immunity. (C) 2003 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: propolis; mitogen-induced proliferation; IFN-gamma; lymphocyte activation